DAMPAK PERUBAHAN LAHAN SAWAH MENJADI OBJEK WISATA LEMPAKE - Astuti, Evi; Juwari, Juwari; Rahmadi, Rahmadi; Sandy, Aisyah Trees (Pusat Kajian Berkelanjutan UIN Sulthan Thaha Saifuddin Jambi, 2024)
Tourism is a sector that has a large role in national development. One example of the development of the tourism sector in the city of Samarinda is the addition of agricultural land. This research aims to determine the role and impact of rice field tourist attractions.Â This research was carried out in Lempake Village, North Samarinda. Research data was collected using observation, interviews and documentation and using qualitative descriptive methods. The results of this research show that the role of the community fully supports the existence of the Sawah Pandang tourist attraction moving in the agricultural sector, which is carried out by the tourist attraction manager and the surrounding community. This tourist attraction collaborates with the community who act as initiators, implementers, providing opinions, and as evaluation monitors in the development of the tourist attraction. The impact on the community around the tourist attraction with this tourism is that in this case it includes environmental conditions where the local community already feels that the environment is the main attraction of tourist activities which positively influences the lives of the surrounding community, opening up many opportunities.